Scanning Tunneling Microscopy Investigations of Interlayer Interaction Induced Superstructures in Transition Metal Dichalcogenides - Molino, Laurent (Université d'Ottawa | University of Ottawa, 2024)
In vertically stacked two-dimensional (2D) materials, interlayer interaction can lead to the formation of superstructures, with properties not present in their constituent parts. These superstructures give rise to new phases of matter, such as charge density waves (CDW), and the many-body physics arising from dispersionless bands in moiré systems. The transition metal dichalcogenides (TMDs) have been of particular recent interest due in part to their reduced symmetry compared to graphene, and their capacity, in the twisted bilayer case, to host nearly dispersionless bands over a broad range of angles. In this thesis, scanning tunneling microscopy (STM) is used to study emergent superstructures in TMDs. A procedure is developed for the fabrication of STM-compatible twisted TMD samples. Using this procedure, a series of samples are produced to study the structural and electronic properties of twisted bilayer WS2 in different moiré regimes. In these samples, we observe in-plane structural reconstruction leading to ferroelectric stacking order domains. We demonstrate local control of the domain wall bending with the STM, and explore the role of anisotropic strain in the domain wall network dynamics. Subsequently, we study a sample in the unreconstructed moiré regime, investigate the role of out-of-plane relaxation on the flat band wavefunctions, and through comparison to first principles techniques, present evidence for the suppression of the moiré buckling in our sample. In addition to the moiré results, the commensurate CDW phase of 1T-TaS2 is observed with STM, and broad spectrum density of states measurements are used alongside Raman spectroscopy to argue for selective electron-phonon coupling and interlayer dimerization in this system. These results contribute to the understanding of the structural and electronic properties of TMDs, moving the field forward toward device applications, including establishing twisted transition metal dichalcogenides as a platform for quantum simulation.
Keywords: condensed matters physics; scanning probe microscopy; two-dimensional materials; nanofabrication; transition metal dichalcogenides; moiré patterns